Pernikahan Dini Dalam Tinjauan Hukum Islam Dan Psikologi - Ihza Habibi, Yusril; Dewi, Tika (Institut Syekh Abdul Halim Hasan Binjai, 2024)
This paper examines how early marriage is a phenomenon that is currently common in Indonesia. The analysis carried out in this paper is to examine the perspective of Islamic law and the psychological perspective of early marriage. The purpose of marriage is according to Islamic teachings and the goodness of the parties directly interested, and on the basis of